The Effect Of Hedonic Value And Utilitarian Value On Purchase Intention With Emotional Pleasure As An Intervening Variable Towards Tiktok Influencers - Shelomitha Azzahra Ade Putri; Nonik Kusuma Ningrum; Lusia Tria Hatmanti Hutami (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the effect of hedonic value and utilitarian value on emotional pleasure, as well as the effect of both variables on purchase intention, with emotional pleasure as an intervening variable. Specifically, this study examines: (1) the effect of hedonic value on emotional pleasure; (2) the effect of utilitarian value on emotional pleasure; (3) the effect of hedonic value on purchase intention; (4) the effect of utilitarian value on purchase intention; and (5) the effect of emotional pleasure on purchase intention among consumers who watch product promotion content through TikTok live streams. The sample in this study consisted of 126 respondents, who were TikTok users in Indonesia that have previously watched product promotion content and showed interest in the promoted products. The sample size determination was based on the multiplication of the total research indicators by a coefficient of 7 (18 × 7 = 126). Data were collected through an online questionnaire distributed via Google Forms and disseminated through social media. The sampling technique used was purposive sampling, with the criteria that respondents must have watched product promotional content through TikTok live commerce. The results indicate that hedonic value has a positive and significant effect on purchase intention, utilitarian value has a positive and significant effect on purchase intention, and emotional pleasure has a positive and significant effect on purchase intention. Furthermore, utilitarian value has a positive and significant effect on emotional pleasure, while hedonic value has a positive but insignificant effect on emotional pleasure. The mediation test results also demonstrate that emotional pleasure significantly mediates the effect of utilitarian value on purchase intention and indirectly mediates the effect of hedonic value on purchase intention.